2018
DOI: 10.1371/journal.pbio.2005239
|View full text |Cite
|
Sign up to set email alerts
|

Descending pathways generate perception of and neural responses to weak sensory input

Abstract: Natural sensory stimuli frequently consist of a fast time-varying waveform whose amplitude or contrast varies more slowly. While changes in contrast carry behaviorally relevant information necessary for sensory perception, their processing by the brain remains poorly understood to this day. Here, we investigated the mechanisms that enable neural responses to and perception of low-contrast stimuli in the electrosensory system of the weakly electric fish Apteronotus leptorhynchus. We found that fish reliably det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 110 publications
(139 reference statements)
2
57
0
Order By: Relevance
“…2018; Metzen et al . 2018), terminate on their apical dendrites (Sas & Maler, 1983, 1987; Berman & Maler, 1999; Deemyad et al . 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2018; Metzen et al . 2018), terminate on their apical dendrites (Sas & Maler, 1983, 1987; Berman & Maler, 1999; Deemyad et al . 2011).…”
Section: Discussionmentioning
confidence: 99%
“…2018; Metzen et al . 2018). As such, the mechanisms by which serotonergic feedback alters ELL pyramidal cell responses to envelopes most likely differ from those of glutamatergic/GABAergic feedback pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rather than relying solely on bottom-up computations, encoding of looming or receding objects is mediated by descending feedback from the midbrain [34]. Similarly, feedback rather than feedforward information processing is involved in extracting electrosensory envelope information, a correlate of distance [46].…”
Section: Discussionmentioning
confidence: 99%
“…The feedback through nP's stellate cells has also been shown to enhance the response to envelope signals elicited by moving conspecifics (Metzen et al, 2018). The authors of this study showed that the sensitivity of a specific electromotor reaction to the envelope signals of medium to low strength (10-15% contrast) required this input.…”
Section: Network Dynamic and Spatial Processingmentioning
confidence: 70%